2009
DOI: 10.1897/08-050.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effects of coal fly ash amendments on the toxicity of a contaminated marine sediment

Abstract: Approaches for cleaning-up contaminated sediments range from dredging to in situ treatment. In the present report, we discuss the effects of amending reference and contaminated sediments with coal fly ash to reduce the bioavailability and toxicity of a field sediment contaminated with polycyclic aromatic hydrocarbons (PAHs). Six fly ashes and a coconut charcoal were evaluated in 7 d whole sediment toxicity tests with a marine amphipod (Ampelisca abdita) and mysid (Americamysis bahia). Fly ashes with high carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…Because of their strong sorption capacities, both CNTs and black carbon have been suggested as potential remediation materials to reduce the bioavailability of HOCs in sediments or soils [7,[13][14][15]. Petersen et al [6] reported that 0.3% CNT amendment in soils decreased pyrene bioaccumulation by earthworm Eisenia fetida.…”
Section: Introductionmentioning
confidence: 99%
“…Because of their strong sorption capacities, both CNTs and black carbon have been suggested as potential remediation materials to reduce the bioavailability of HOCs in sediments or soils [7,[13][14][15]. Petersen et al [6] reported that 0.3% CNT amendment in soils decreased pyrene bioaccumulation by earthworm Eisenia fetida.…”
Section: Introductionmentioning
confidence: 99%
“…The time of AC treatment varied from two minutes (Sun and Ghosh, 2007) to 780 days (Tomaszewski et al, 2007). In some articles, this information was not available (Voparil et al, 2004;Cornelissen et al, 2006a;Burgess et al, 2009). The work of Sun and Ghosh (2007) was specifically investigating the time of AC treatment.…”
Section: Reduction Of Endpoint's Concentration In Sedimentsmentioning
confidence: 99%
“…Therefore, researchers started to use alternative carbon material like e.g. biochar (Yu et al, 2009), coke breeze (Zimmerman et al, 2004;Millward et al, 2005), waste AC (Guo et al, 1991), fly ash (Burgess et al, 2009), and many more. Further drawbacks and side effects of AC amendment, such as the stability of the AC material, physical alteration of the matrices, direct or indirect harmful effects on, and nutrient availability to organisms will be discussed in "Factors potentially reducing the efficiency of AC amendment and other side effects" section.…”
Section: Introductionmentioning
confidence: 99%
“…The levels of PAH associated with a fly ash are, however, a very strong function of the temperature and excess oxygen used in combustion [46], and the levels from pulverized coal combustion power plants are typically quite low (Wornat et al [47] found levels of typical 2- to 3-ring PAH in the range of ppb and below). In fact, these inherent PAH levels are usually sufficiently low, suggesting that coal combustion fly ashes might themselves be useful for binding (adsorbing) PAH from other sources and residing in marine sediments [48]. Fly ash has also been considered as an inexpensive adsorbent for water or soil treatment, such as for adsorption of aromatic acid dyes [49].…”
Section: Evolution Of Unburned Carbon In Coal-fired Power Plantsmentioning
confidence: 99%